A facile method to prepare superparamagnetic iron oxide and hydrophobic drug-encapsulated biodegradable polyurethane nanoparticles - Cheng K (Dove Medical Press, 2017)
Kuo-Wei Cheng, Shan-hui Hsu Institute of Polymer Science and Engineering, College of Engineering, National Taiwan University, Taipei, Taiwan, Republic of China Abstract: Superparamagnetic iron oxide nanoparticles (SPIO NPs) have a wide range of biomedical applications such as in magnetic resonance imaging, targeting, and hyperthermia therapy. Aggregation of SPIO NPs can occur because of the hydrophobic surface and high surface energy of SPIO NPs. Here, we developed a facile method to encapsulate SPIO NPs in amphiphilic biodegradable polymer. Anionic biodegradable polyurethane nanoparticles (PU NPs) with ~35 nm size and different chemistry were prepared by waterborne processes. SPIO NPs were synthesized by chemical co-precipitation. SPIO NPs were then added to the aqueous dispersion of PU NPs, followed by application of high-frequency (~20 kHz) ultrasonic vibration for 3 min. This method rendered SPIO-PU hybrid NPs (size ~110 nm) suspended in water. SPIO-PU hybrid NPs contained ~50–60 wt% SPIO and retained the superparamagnetic property (evaluated by a magnetometer) as well as high contrast in magnetic resonance imaging. SPIO-PU NPs also showed the ability to provide cell hyperthermic treatment. Using the same ultrasonic method, hydrophobic drug (Vitamin K3 [VK3]) or (9-(methylaminomethyl)anthracene [MAMA]) could also be encapsulated in PU NPs. The VK3-PU or MAMA-PU hybrid NPs had ~35 nm size and different release profiles for PUs with different chemistry. The encapsulation efficiency for VK3 and MAMA was high (~95%) without burst release. The encapsulation mechanism may be attributed to the low glass transition temperature (Tg) and good mechanical compliance of PU NPs. The new encapsulation method involving waterborne biodegradable PU NPs is simple, rapid, and effective to produce multimodular NP carriers. Keywords: superparamagnetic iron oxide, polyurethane, drug release, hybrid nanoparticles